Macroporous scaffold surface modified with biological macromolecules and piroxicam-loaded gelatin nanofibers toward meniscus cartilage repair - Abpeikar, Zahra; Javdani, Moosa; Mirzaei, Seyed Abbas; Alizadeh, Akram; Moradi, Lida; Soleimannejad, Mostafa; Bonakdar, Shahin; Asadpour, Shiva (International journal of biological macromolecules, 2021)
Meniscus cartilage has poor self-healing capacity in the inner zone and its damage leads to articular cartilage degeneration. Here we have developed hybrid constructs using polycaprolactone (PCL) and polyurethane (PU) surface modified by gelatin (G), chitosan (C), and hyaluronic acid (H) biomacromolecules and piroxicam-loaded gelatin nanofibers (PCL/PU/GCH/P). The surface of constructs was crosslinked using EDC and NHS. The scaffolds were investigated by SEM, FTIR spectroscopy, swelling test, degradation rate, mechanical tests, and in vitro piroxicam release assay. Furthermore, the cell-seeded scaffolds were evaluated by SEM, viability assay, dapi staining, cell migration, proliferation, and gene expression of chondrocytes within these scaffolds. Finally, the animal study was performed in a rabbit model. Chondrocyte and rabbit adipose-derived mesenchymal stem cells (ASCs) from the infrapatellar fat pad (Hoffa's fat pad) were used. Swelling and degradation rate were increased in the modified scaffolds. Tensile and compressive Young's modulus also were near to human native meniscus tissue. The highest expression level of chondrocyte marker genes was observed for the PCL/PU/GCH scaffold. A significant regeneration was obtained in rabbits treated with ASCs-loaded PCL/PU/GCH/P scaffold after 3 months. The surface-modified scaffolds with or without ASCs could successfully accelerate meniscus regeneration and exhibit potential application in meniscus tissue engineering. Scaffold fabrication, scaffold and cell-scaffold characterization, implantation of the tissue-engineered meniscus constructs in a rabbit partial meniscectomy model. ASCs-seeded PCL/PU/GCH scaffold successfully regenerated partial meniscus injury in the rabbit model. PCL: polycaprolactone; PU: polyurethane; G: Gelatin; C: chitosan; H: hyaluronic acid; P: piroxicam; EDC: 1-ethyl-3-(3-dimethyl-aminopropyl)-1-carbodiimide hydrochloride; NHS: N-hydroxy succinimide. [Display omitted] •Surface modification of the scaffolds with the hydrophilic biopolymers increased swelling, degradation rate, and mechanical strength.•All scaffolds were biocompatible.•The level of cell proliferation and migration on the surface-modified scaffolds was higher.•Loading piroxicam into the nanofibers caused a relatively stable and gradual release of the drug from the scaffold.•The highest expression level of chondrocyte marker genes was seen in the PCL/PU/GCH scaffold.•The surface-modified scaffolds with or without ASCs successfully regenerated partial meniscus injury in the rabbit model.